2021
DOI: 10.1007/s12325-020-01607-4
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Healthcare Resource Use Associated with Risk of Cardiovascular Morbidity in Patients with Chronic Kidney Disease: Evidence from a Systematic Literature Review

Abstract: Introduction The management of chronic kidney disease (CKD) costs in excess of $114 billion in the USA and £1.45 billion in the UK annually and is projected to increase alongside the increasing disease prevalence. The aim of this review was to evaluate the risks of cardiovascular (CV) morbidity, CV mortality or all-cause mortality based on KDIGO (Kidney Disease: Improving Global Outcomes) 2012 categorisations and estimate the additional costs and healthcare resource utilisation associated with CV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Different studies have shown that health care costs increase as renal function worsens or albuminuria develops, particularly in patients that finally require kidney replacement therapy [ 5 , 11 14 , 16 , 20 , 44 – 46 ]. As a result, although renal replacement therapy has been the object of constant analysis in order to improve the efficiency and sustainability, the fact is that preventing the occurrence and progression of CKD is the best way to reduce health care resource consumption and health care costs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Different studies have shown that health care costs increase as renal function worsens or albuminuria develops, particularly in patients that finally require kidney replacement therapy [ 5 , 11 14 , 16 , 20 , 44 – 46 ]. As a result, although renal replacement therapy has been the object of constant analysis in order to improve the efficiency and sustainability, the fact is that preventing the occurrence and progression of CKD is the best way to reduce health care resource consumption and health care costs.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, although renal replacement therapy has been the object of constant analysis in order to improve the efficiency and sustainability, the fact is that preventing the occurrence and progression of CKD is the best way to reduce health care resource consumption and health care costs. Therefore, interventions designed to minimize decline in progressive kidney function, particularly among patients with stage 3 or 4 CKD, may reduce the economic CKD burden [ 5 , 11 14 , 16 , 20 , 44 – 47 ]. It has been reported that the addition of RAAS inhibitors to prevent the advance of nephropathy is worthwhile not only from a clinical perspective, but also from an economic point of view, even in patients with end stage renal disease, mainly driven by a reduction of hospitalization costs [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CKD patients suffer from excess cardiovascular and all-cause mortality [2, 3]. Recognition of high-risk patients could lead to a different approach, treatment, better outcome, and lower health-care cost [4, 5].…”
Section: Introductionmentioning
confidence: 99%